Human resource development : strategy and tactics - Swart, Juani (Elsevier Butterworth Heinemann, 2005)
Each chapter in Human Resource Development provides the reader with commentary, activities and review sections in an integrated approach. The action-oriented approach is vital for practicing managers but increasingly for postgraduate and final year undergraduates who have work experience. It is this aspect of the book that fills a gap that currently exists in the market. This text reflects organizational realities and balances and integrates the coverage of individuals, teams and organizational learning. The book is written in a straightforward manner and explains concepts and key issues in.